Subtidal Microphytobenthos: A Secret Garden Stimulated by the Engineer Species Crepidula fornicata - Androuin, Thibault; Polerecky, Lubos; Decottignies, Priscilla; Dubois, Stanislas F.; Dupuy, Christine; Hubas, Cédric; Jesus, Bruno; Le Gall, Erwan; Marzloff, Martin P.; Carlier, Antoine (Frontiers in Marine Science, 2018)
The slipper limpet Crepidula fornicata is an emblematic invasive species along the northeast Atlantic coast. This gregarious gastropod lives in stacks of several individuals and forms extended beds in shallow subtidal areas. The effects of this engineer species on the colonized habitat can be physical (e.g., presence of hard-shell substrates with uneven topography) or biological (e.g., nutrient enrichment by direct excretion or via biodeposition). We hypothesized that through biological activity, nutrient fluxes at the sediment-water interface are enhanced, leading to stimulated primary productivity by microphytobenthos (MPB) associated with Crepidula beds. To test this fertilization hypothesis, we conducted a 10-day mesocosm experiment using C. fornicata (live and dead) placed on top of sieved and homogenized sediment collected in situ. We used hyperspectral imaging to non-invasively map the development of MPB biomass, and to assess the potential influence of C. fornicata and its spatial extent. Our results showed that live C. fornicata significantly promote MPB growth through both physical and biological effects, with the biological effect dominating over the pure physical one. The highest stimulation was observed on the shells, suggesting that dissolved metabolic products excreted by C. fornicata were likely the main factor stimulating MPB growth in our short-term experiment. Our findings provide first direct evidence that stimulation of MPB growth by the biological activity of larger benthic epifauna occurs not only in intertidal but also in shallow subtidal habitats. More research is needed to assess the contribution of this fertilization effect to the trophic functioning of subtidal benthic systems.